UPAYA KERJA SAMA MANAJEMEN BENCANA FILIPINA DENGAN THE ASEAN COORDINATING CENTRE FOR HUMANITARIAN AND DISASTER MANAGEMENT (AHA CENTRE) DALAM MENINGKATKAN PLACE BRANDING NEGARA PASCA TOPAN HAIYAN 2013 - Haryani, Zumratul; Sushanti, Sukma; Dharmiasih, D.A Wiwik (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
This research aims to describe the Philippines' collaborative disaster management efforts with AHA Center to improving the country's place branding using qualitative methods. The natural disaster of Typhoon Haiyan in 2013 has damaged the Philippines' place branding. This effort to maintain the reputation of the Philippines as a country that has international tourism potential. The disaster prompted the Philippine government to collaborate in disaster management with the AHA Center to improve place branding after Typhoon Haiyan 2013. Therefore, researchers used a framework with the concept of regional disaster management and the place branding concept. The concept to answer The Philippines' collaboration in disaster management efforts with the AHA Center to improving place branding. This research found an answer, were several collaborative efforts wares made by the Philippines with the AHA Center to improving place branding after the occurrence of Typhoon Haiyan in 2013. Keyword : Philippines, Regional Disaster Management, Place Branding, Typhoon Haiyan, AHA Centre.